The Role of Political Connections in Moderating the Relationship of Profit Management and Company Values (Study on State Owned Enterprises) - PAKAWARU, Muhammad Ilham; RIDWAN, Ridwan; BAKRY, M.Iqbal; MULIATI, Muliati; PARWATI, Ni Made Suwitri (Journal of Governance, Taxation and Auditing, 2023)
This study examines the role of political correction in moderating the relationship between earnings management and firm value during the Joko Widodo and Jusuf Kalla administrations in the 2015-2019 period. Political connections are measured by the activeness of meetings attended by the Board of Commissioners (main commissioners, commissioners and independent commissioners) who are politically connected. Earnings management uses discretionary accruals while firm value uses the Tobins Q proxy. There are 18 state-owned companies (BUMN) that are sampled in the study with 5 years of observation. By using warpPLS7.0, the results show that earnings management reduces firm value and political connections positively moderate the relationship between earnings management and firm value